2010
DOI: 10.1155/2010/831658
|View full text |Cite
|
Sign up to set email alerts
|

Cellulose Acetate Sulfate as a Lyotropic Liquid Crystalline Polyelectrolyte: Synthesis, Properties, and Application

Abstract: The optimal conditions of cellulose acetate sulfate (CAS) homogeneous synthesis with the yield of 94–98 wt.% have been determined. CAS was confirmed to have an even distribution of functional groups along the polymer chain. The polymer was characterized by an exceptionally high water solubility (up to 70 wt.%). The isothermal diagrams of its solubility in water-alcohol media have been obtained. CAS aqueous solutions stability, electrolytic, thermal, and viscous properties have been defined. The main hydrodynam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 17 publications
1
12
0
4
Order By: Relevance
“…The intense band at 1624 cm -1 is assigned to absorbed water [52]. Cationic hemicelluloses [21] Cellulose acetate sulfate [35] Polyacrylamide [50] Figure 2. FT-IR spectra of polyelectrolytes…”
Section: Results and Discussion 31 Characterization Of Polymersmentioning
confidence: 99%
See 2 more Smart Citations
“…The intense band at 1624 cm -1 is assigned to absorbed water [52]. Cationic hemicelluloses [21] Cellulose acetate sulfate [35] Polyacrylamide [50] Figure 2. FT-IR spectra of polyelectrolytes…”
Section: Results and Discussion 31 Characterization Of Polymersmentioning
confidence: 99%
“…Cellulose acetate sulfate (CAS) is a water-soluble polymer, produced from acetylation and sulfation carried out simultaneously and it was first synthesized by Chauvelon et al [34]. Cellulose derivatives, having strong polyelectrolytes properties, can be prepared by introducing a greater amount of HOSO 2 O substituents into the chain [35]. Grinshpan et al [35] observed that the cellulose acetate sulfate possessed a unique combination of properties, like an ability to disperse in water spontaneously, forming stable suspensions with narrow particles size distribution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In solution, cellulose derivatives, such as hydroxypropyl cellulose, ethyl cellulose, and cellulose diacetate and triacetate, have the potential to develop LC order with an anisometric macromolecules arrangement, depending on the presence of a relevant solvent and of a certain critical polymer concentration. [1] As the science and technology of polymer blends advances, an increasing number of polymer blend systems and applications continue to be developed. Understanding of the mechanisms involved in polymers mixing, starting from their fundamental interactions, and of the manner in which they affect their final properties, has been possible due to the improvement of characterization techniques.…”
Section: Introductionmentioning
confidence: 99%
“…A presença de grupos sulfato confere elevadas propriedades hidrofílicas aos derivados de celulose e, portanto, tornam-se solúveis em água pelo grau de substituição (GS) tão baixo quanto 0,4-0,6. Derivados de celulose, possuindo propriedades de polieletrólitos fortes, podem ser preparados pela introdução de uma quantidade maior de substituintes HOSO2O (Grinshpan et al, 2010). O uso de extração por membrana é benéfico por minimizar o volume de água utilizada, evitando efetivamente a ocorrência de emulsificação durante o passo de lavagem, resultando numa diminuição da perda de éster metílico durante o processo de purificação (Daud et al, 2015).…”
Section: Sulfato De Acetato De Celuloseunclassified